Malignant degeneration of cystic teratoma of the ovary: two cases report - Hmila, Asma; Taheri, Hafsa; Saadi, Hanane; Mimouni, Ahmed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
The malignant degeneration of mature ovarian teratomas is a rare phenomenon. Case reported two cases of squamous cell carcinoma developed on mature teratoma of the ovary in patients aged 54 and 41 who were seen for chronic pelvic pain. Their pelvic ultrasound showed cystic double-component images with sizes of 103 and 95 mm respectively suggestive of dermoid cysts, and the anatomopathological study of the pieces of adnexectomy confirmed the diagnosis. Although no clinical, radiological or biological signs are specific, ovarian dermal cyst degeneration is suspected in the presence of a large dermoid cyst in a postmenopausal or peri-menopausal woman. The careful anatomo-pathological study of the cyst in this case makes it possible to pose the diagnosis of certainty. A rare complication of the dermoid cyst, its prognosis is pejorative and depends mainly on its clinical stage at the time of diagnosis and the quality of its surgical treatment which must be as radical as possible.